On the K and KG fading channels - Aleksić Danijela (Serbian Journal of Electrical Engineering, 2009)
In this paper, the composite Rayleigh-Gamma and Nakagami-Gamma distributions are considered. Multipath short-term fading and long-term fading (shadowing) affect wireless channels. A composite fading model was proposed for the modeling of shadowed channels, which resulted in a closed form solution for the probability density function (pdf). These composite Rayleigh-Gamma and Nakagami-Gamma are well-known as the K-distribution and KG-distribution, and are applied to cases where both micro- and macro-diversity schemes are implemented to mitigate short-term fading and shadowing, respectively. Thus, the composite pdf model offers significant improvement over approaches, which use lognormal pdf for shadowing. The results demonstrate the simplicity and usefulness of the composite pdf in the performance analyses of shadowed fading channels.